Graphene-Reinforced Titanium Enhances Soft Tissue Seal - Wei, Jianxu; Qiao, Shichong; Zhang, Xiaomeng; Li, Yuan; Zhang, Yi; Wei, Shimin; Shi, Junyu; Lai, Hongchang (Frontiers in Bioengineering and Biotechnology, 2021)
The integrity of soft tissue seal is essential for preventing peri-implant infection, mainly induced by established bacterial biofilms around dental implants. Nowadays, graphene is well-known for its potential in biocompatibility and antisepsis. Herein, a new titanium biomaterial containing graphene (Ti-0.125G) was synthesized using the spark plasma sintering (SPS) technique. After material characteristics detection, the subsequent responses of human gingival fibroblasts (HGFs) and multiple oral pathogens (including Streptococci mutans, Fusobacterium nucleatum, and Porphyromonas gingivalis) to the graphene-reinforced sample were assessed, respectively. Also, the dynamic change of the bacterial multispecies volume in biofilms was evaluated using absolute quantification PCR combined with Illumina high-throughput sequencing. Ti-0.125G, in addition to its particularly pronounced inhibitory effect on Porphyromonas gingivalis at 96 h, was broadly effective against multiple pathogens rather than just one strain. The reinforced material's selective responses were also evaluated by a co-culture model involving HGFs and multiple strains. The results disclosed that the graphene-reinforced samples were highly effective in keeping a balance between the favorable fibroblast responses and the suppressive microbial growth, which could account for the optimal soft tissue seal in the oral cavity. Furthermore, the underlying mechanism regarding new material's bactericidal property in the current study has been elucidated as the electron transfer, which disturbed the bacterial respiratory chain and resulted in a decrease of microbial viability. According to the Kyoto Encyclopedia of Genes and Genomes (KEGG) database, the PICRUSt tool was conducted for the prediction of microbial metabolism functions. Consequently, it is inferred that Ti-0.125G has promising potentials for application in implant dentistry, especially in enhancing the integrity of soft tissue and improving its resistance against bacterial infections around oral implants.